The below examples show that the method of factorizing ax^{2} + bx + c by breaking the middle term involves the following steps.
Steps:
1.Take the product of the constant term and the coefficient of x^{2}, i.e., ac.
2. Break ac into two factors p, q whose sum is b, i.e., p + q = b.
3. Pair one of them, say px, with ax^2 and the other, qx, with c. Then factorize the expression.
Solved Examples on Factorization of Expressions of the Form ax^2 + bx + c, a ≠ 1:
1. Factorize: 6m^{2} + 7m + 2.
Solution:
Here, 6 × 2 = 12 = 3 × 4 and, 3 + 4 = 7 (= coefficient of m).
Therefore, 6m^{2} + 7m + 2 = 6m^{2} + 3m + 4m + 2
= 3m(2m + 1) + 2(2m + 1)
= (2m + 1)(3m + 2)
2. Factorize: 1 – 18x – 63x^{2}
Solution:
The given expression is – 63x^{2} - 18x + 1
Here, (-63) × 1 = -63 = (-21) × (3), and -21 + 3 = -18(= coefficient of x).
Therefore, – 63x^{2} - 18x + 1 = – 63x^{2} – 21x + 3x + 1
= -21x(3x + 1) + 1(3x + 1)
= (3x + 1)(-21x + 1)
= (1 + 3x)(1 – 21x).
3. Factorize: 6x^{2} – 7x – 5.
Solution:
6 × (-5) = -30 = (-10) × (3), and -10 + 3 = - 7 (= coefficient of x).
Therefore, 6x^{2} – 7x – 5 = 6x^{2} – 10x + 3x – 5
= 2x(3x – 5) + 1(3x – 5)
= (3x – 5)(2x + 1)
4. Factorize: 30m^{2} + 103mn – 7n^{2}
Solution:
30 × (-7) = -210 = (105) × (-2), and 105 + (-2) = 103 (= coefficient of mn).
Therefore the given expression, 30m^{2} + 103mn – 7n^{2}
= 30m^{2} + 105mn – 2mn – 7n^{2}
= 15m(2m + 7n) – n(2m + 7n)
= (2m + 7n)(15m – n)
From Factorization of Expressions of the Form ax^2 + bx + c, a ≠ 1 to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Feb 28, 24 04:07 PM
Feb 28, 24 01:43 PM
Feb 27, 24 02:43 PM
Feb 24, 24 04:11 PM
Feb 24, 24 04:10 PM
New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.